An Interdisciplinary Approach to Endometriosis-associated Persistent Pelvic Pain. Issue 2 (2017) - Allaire, Catherine; Aksoy, Tuba; Bedaiwy, Mohamed; Britnell, Susannah; Noga, Heather L.; Yager, Holly; Yong, Paul J.
Endometriosis-associated pelvic pain is a common and often challenging problem. For certain patients, pain persists or recurs despite adequate medical or surgical therapy targeted to endometriosis. In this patient population, there is often the presence of coexisting pain conditions such as irritable bowel syndrome, painful bladder syndrome and myofascial pain as well central sensitisation. An interdisciplinary approach where both peripheral pain triggers and central sensitization are addressed is likely to lead to improved pain and quality of life. The approach to the evaluation and treatment of the patients with persistent/chronic pelvic pain and endometriosis is outlined in this article.